Analysis of Confidence, Emotional Regulation, and Discipline Levels Among Elite Karate and Sepaktakraw Athletes of South Sulawesi - Nawir, Nukhrawi; Hamid, Muflih Wahid (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research explores the levels of self-confidence, emotional regulation, and discipline in achieving goals among Karate and Sepaktakraw athletes in South Sulawesi. Using a mixed-method approach that combines surveys and structured observations, the study examines psychological characteristics and their impact on athletic performance. Data were collected from selected athletes through questionnaires and direct observations conducted during training sessions and competitions. The results indicate that self-confidence, emotional control, and goal commitment are key contributors to performance outcomes. However, despite the majority of athletes demonstrating high levels in these variables, notable variations were found, particularly among Karate athletes. Some exhibited moderate levels of emotional regulation and discipline, suggesting that individual differences may influence these traits. Such findings underline the importance of tailored psychological interventions that cater to the unique needs of athletes in different sports disciplines. This study emphasizes the necessity of integrating psychological training into coaching programs to enhance mental resilience, focus, and consistency in performance. By adopting a holistic coaching approach that addresses both physical and psychological dimensions, coaches can better support athletes in achieving peak performance at national and international levels. The insights from this research provide valuable guidance for sports practitioners, enabling the development of evidence-based strategies to optimize athletic potential through a deeper understanding of psychological factors.